Pengaruh Penambahan Starter Lactobacillus plantarum Terhadap Karakteristik Organoleptik Dadih Susu Sapi - Dwiannisa, Stella; Habibah, Habibah; Archadiya, Meilan; Wulandari, Afiza (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2025)
The aim of this research is to examine the effect of different concentrations of Lactobacillus plantarum starter culture on the organoleptic characteristics of cow milk dadih. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatments included untreated cow milk dadih (P0), cow milk dadih with the addition of Lactobacillus plantarum starter at concentrations of 2% (P1), 3% (P2), 4% (P3), and 5% (P4). The material used in this study was cow’s milk. The observed variables were organoleptic characteristics (color, texture, aroma, taste, and level of preference) assessed through a hedonic test by 10 panelists. The data obtained were analyzed using the non-parametric Kruskal-Wallis comparative test. If the Kruskal-Wallis test showed significant differences, it was followed by the Mann-Whitney test to identify which treatments differed significantly. Statistical analysis was conducted using SPSS software. The analysis results showed that the addition of Lactobacillus plantarum had no significant effect on the color and taste of the dadih (P>0.05), but had a significant effect on texture, aroma, and level of preference (P<0.05). It was concluded that the addition of Lactobacillus plantarum starter at a concentration of 3% (P2) was the best treatment, providing a stronger aroma, a texture closer to panelist preferences, and the highest level of preference compared to the other treatments.